2013
DOI: 10.1016/j.molcel.2012.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome-Driven Transcription Factor Binding and Gene Regulation

Abstract: Elucidating the global function of a transcription factor implies the identification of its target genes and genomic binding sites. The role of chromatin in this context is unclear, but the dominant view is that factors bind preferentially to nucleosome-depleted regions identified as DNaseI-hypersensitive sites (DHS). Here we show by ChIP, MNase, and DNaseI assays followed by deep sequencing that the progesterone receptor (PR) requires nucleosomes for optimal binding and function. In breast cancer cells treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
165
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(192 citation statements)
references
References 56 publications
(67 reference statements)
25
165
2
Order By: Relevance
“…Whole genome expression microarrays with cells stimulated for different times with Pg reveals around 4,000 hormone target genes, half of them upregulated and the other half downregulated. 2 The nature of the regulated genes is concordant with previous reports demonstrating a proliferative burst induced by progesterone in breast cancer cells. 13 Comparison of gene expression results with PR occupancy in response to hormone shows a significant enrichment of PRbs around Pg upregulated genes, which correlates with the magnitude of hormone response.…”
Section: Pr Binding Sites Are Marked By High Nucleosomes Occupancysupporting
confidence: 89%
See 2 more Smart Citations
“…Whole genome expression microarrays with cells stimulated for different times with Pg reveals around 4,000 hormone target genes, half of them upregulated and the other half downregulated. 2 The nature of the regulated genes is concordant with previous reports demonstrating a proliferative burst induced by progesterone in breast cancer cells. 13 Comparison of gene expression results with PR occupancy in response to hormone shows a significant enrichment of PRbs around Pg upregulated genes, which correlates with the magnitude of hormone response.…”
Section: Pr Binding Sites Are Marked By High Nucleosomes Occupancysupporting
confidence: 89%
“…Indeed, the PRbs show an enrichment of binding sites for members of several TF families, but none of them was significant enough to explain the large discrepancy between potential PRbs and actually bound sites. 2 Previous reports have shown that receptors for other steroid hormone bind preferentially to sites within regions of "open" chromatin, detected as DNaseI hypersensitive sites (DHS), 14 which are usually represented as depleted of nucleosome. We used DNaseI-sequencing (DNaseI-Seq) to determine genome wide the location of DHS in T47D-MTVL cells before and after hormone treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most transcription factors cannot access nucleosomal DNA by themselves, pioneer transcription factors (e.g., FoxA) can bind to nucleosomal DNA and recruit other factors to bind (Cirillo et al 2002). Along these lines, the transcription factors p53 and PU.1 and the progesterone receptor, which apparently operates with FoxA1 (Clarke and Graham 2012), preferentially target their binding motifs amid sequences with high intrinsic nucleosome occupancy rather than high-affinity motifs with low intrinsic nucleosome occupancy (Lidor Nili et al 2010;Ballare et al 2013;Barozzi et al 2014). Thus, contrary to the dogma that nucleosomes would be inherently repressive to gene activity and must be removed for factor binding, pioneer transcription factors positively use the feature of high nucleosome occupancy at enhancers as their functional binding target ( Fig.…”
Section: Nucleosomes At Enhancers: a Collaborator For Pioneer Factorsmentioning
confidence: 99%
“…Indeed, the elegant demonstration of progesterone receptor binding to nucleosome PRE, recently published (35), further challenges this view. Our results are consistent with a model where ERα, in the absence of estrogen stimulation, collaborates with other transcription factors to maintain the luminal epithelial enhancer landscape.…”
Section: Significancementioning
confidence: 99%